Mobility of As, Cr and Cu in a contaminated grassland soil in response to diverse organic amendments; a sequential column leaching experiment. (January 2018) - Mitchell, Kerry; Trakal, Lukas; Sillerova, Hana; Avelar-González, Francisco Javier; Guerrero-Barrera, Alma Lilian; Hough, Rupert; Beesley, Luke
Abstract: Sequential column leaching coupled with batch sequential extraction assays were used to assess the fate of arsenic, chromium and copper in a wood ash contaminated grassland soil amended with biochar and its non-pyrolysed origin source material. Application of both amendments resulted in a general reduction of copper and arsenic mobility. Chromium, confirmed to be highly mobile under the elevated pH conditions of the experimental soil, was also stabilised with both amendments, though its mobility was more significantly reduced in soils amended with the source material. This was attributable in part to lower pH in the source material amended soils when compared to the biochar amended soils which facilitated the reduction of the more mobile chromium (VI) to less mobile chromium (III), as confirmed by ion exchange chromium speciation. In this study, the use of biochar vs source material was beneficial only for select metals, thus highlighting the importance of considering the specific physico-chemical conditions and metal (loid) properties in contaminated soils during the evaluation of the suitability of individual materials for onward remediation actions. Highlights: Source material and its resultant biochar were applied to a metal (loid) contaminated agricultural soil. Sequential and static leaching assays were performed to evaluate geochemical fate of As, Cr and Cu. Application of both amendments reduced Cu and As mobility due to co-precipitation/association with organic matter. Source material application resulted in reduced pH, and a shift in speciation from Cr (VI) to Cr(III). For selected metals, source material appears to be advantageous over biochar in terms of environmental risk exposure.